THE INFLUENCE OF UMKM ON THE USE OF SOCIAL MEDIA MARKETING IN THE MIDDLE OF THE COVID-19 CRISIS - Muhammad Nurhidayat Muis; Ariq salman; firhan mulia (Jurnal Ekonomi Trisakti, 2023)
Purpose – This research has the aim of knowing whether there is an influence of MSMEs on the use of social media marketing in the middle of the covid-19 crisis Design/methodology/approach – The approach used in this research is to use a quantity approach and a simple random sampling methodology. Data were collected through the distribution of online questionnaires, and the results of testing the hypothesis with multiple regression analysis were applied to 47 responses given by respondents. Findings – In this study, all hypotheses have a positive and significant effect on Perceived usefulness, Attitude towards usage, and Behavioral intention of social media. Of Social Media Marketing among MSMEs during the COVID-19 crisis. Originality/value – Surveys are done because the author wants to know the population's trends, behaviour, or opinions by studying a sample of the target population, where the authors wish to find out the opinions of MSME actors related to use social media for marketing. Keywords – Perceived ease of use, Perceived usefulness, Attitude towards usage of social media marketing, Behaviour intention for using social media marketing. Paper type – Research paper.